PERANCANGAN IKLAN LAYANAN MASYARAKAT TENTANG KESEJAHTERAAN KUCING LIAR DALAM MEDIA AUDIO VISUAL - ADI SAPUTRA, Drs. Syafwan, M.Si., San Ahdi, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Cat welfare is a reflection of human care and treatment in improving the quality of life in cats, the community is encouraged to develop empathy and respect for cats as animals that live in the communityThe purpose of designing public service announcement of cat welfare through audio-visual media that is emotionally memorable is to educate about humanity and empathy in the community, especially adults, so they can teach children the goodness and improve the quality of cat life.The design method used in this public service announcement is the glassbox method, and data collection is done using the observation and questionnaire method. Data analysis method using 5W + 1H technique (what, why, who, when, where + how). The design of this public service announcement is also supported by several media such as posters, T-shirts, key chains, mugs, totebags, stickers and also a simple cat house as the media support.The results achieved are the audio-visual media of cat welfare which is broadcasted and distributed through YouTube that can be an easy to access in accordance to the target.Keyword : Public Service Announcement, Audio visual, Cat Welfare